Pre-implementation adaptation of suicide safety planning intervention using peer support in rural areas - Woodward, Eva N.; Lunsford, Amanda; Brown, Rae; Downing, Douglas; Ball, Irenia; Gan-Kemp, Jennifer M.; Smith, Anthony; Atkinson, Olympia; Graham, Thomas (Frontiers in Health Services, 2023)
Introduction: There are disparities in suicide behavior and access to preventative treatment. One disparity is the suicide rate in rural areas, including the state of Arkansas-suicide deaths among rural veterans increased 48% the last two decades, double that of urban veterans. One major challenge for veterans in rural areas is lack of healthcare providers to provide Safety Planning Intervention, which is an effective intervention to reduce suicide attempts. One solution is more broadly implementing Safety Planning Intervention, by using peers to deliver the intervention in rural communities. Before implementation, the intervention needs to be adapted for peer-to-peer delivery, and barriers and facilitators identified. Methods: Using community-based participatory research, we adapted Safety Planning Intervention for peer-to-peer delivery in rural communities and identified implementation barriers and facilitators. From July 2022 to February 2023, we conducted group interviews with 12 participants: rural veterans with prior suicidal thoughts or attempts in one U.S. state, their support persons, and healthcare professionals with relevant expertise. We collected qualitative data through interviews during nine, two-hour meetings, and quantitative data from one anonymous survey and real-time anonymous voting. Questions about adaptation were designed according to processes in the ENGAGED for CHANGE community-engaged intervention framework and questions about facilitators and barriers were designed according to the Health Equity Implementation Framework. Participants categorized Safety Planning Intervention components by how freely they could be adapted, using the metaphor of a traffic light in red (do not change), yellow (change with caution), and green (change freely) categories. Results: Participants made few adaptations (categorized in the FRAME modification system), but strongly recommended robust training for peers. Participants identified 27 implementation facilitators and 47 barriers. One example facilitator was some state counties already had veteran crisis programs that could embed this intervention. One example barrier was that some community organizations that might spread the intervention have been motivated initially, yet unable to sustain interventions. Discussion: Our results provide one of the more comprehensive pre-implementation assessments to date for Safety Planning Intervention in any setting, especially for peer delivery outside clinical settings. One important next step will be mapping barriers and facilitators to implementation strategies.